On an edition of ecclesiastical books catalogues between XVIth and XVIIth centuries. Reflections and research purposes - Manfredi, Antonio (Bibliothecae.it, 2016)
Some extant inventories and book-lists, produced between the end of the sixteenth century and the very beginning of the seventeenth century by Religious Orders, in order to comply with the regulations issued by the Sacra Congregatio de Indice ‒ aimed at dressing up a comprehensive catalogue of prohibited books ‒ are the main focus of at least three volumes recently released by the Vatican Library. Thus, a plenty of materials are now available, which enable us to scrutinize both purposes and goals of such an editorial enterprise. Text-critical criteria and philological methods, applied by the Authors throughout the aforementioned volumes, are here examined, with special regard to quantitative relevance of listed items.